Methane-cycling microbial communities in permafrost affected soils on Herschel Island and the Yukon Coast, Western Canadian Arctic - Frank-Fahle, Béatrice A. (2013)
Permafrost-affected ecosystems including peat wetlands are among the most obvious regions in which current microbial controls on organic matter decomposition are likely to change as a result of global warming. Wet tundra ecosystems in particular are ideal sites for increased methane production because of the waterlogged, anoxic conditions that prevail in seasonally increasing thawed layers. The following doctoral research project focused on investigating the abundance and distribution of the methane-cycling microbial communities in four different polygons on Herschel Island and the Yukon Coast. Despite the relevance of the Canadian Western Arctic in the global methane budget, the permafrost microbial communities there have thus far remained insufficiently characterized. Through the study of methanogenic and methanotrophic microbial communities involved in the decomposition of permafrost organic matter and their potential reaction to rising environmental temperatures, the overarching goal of the ensuing thesis is to fill the current gap in understanding the fate of the organic carbon currently stored in Artic environments and its implications regarding the methane cycle in permafrost environments. To attain this goal, a multiproxy approach including community fingerprinting analysis, cloning, quantitative PCR and next generation sequencing was used to describe the bacterial and archaeal community present in the active layer of four polygons and to scrutinize the diversity and distribution of methane-cycling microorganisms at different depths. These methods were combined with soil properties analyses in order to identify the main physico-chemical variables shaping these communities. In addition a climate warming simulation experiment was carried-out on intact active layer cores retrieved from Herschel Island in order to investigate the changes in the methane-cycling communities associated with an increase in soil temperature and to help better predict future methane-fluxes from polygonal wet tundra environments in ...